Letter to My City - Aghedo, Nyami (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
In this poem-letter the speaker addresses their hometown, a place of familiarity and contradiction. Through exploring the dark past of Southern North Carolina an intimate account of living in community is illustrated.